If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 6w = 0 Solving 12 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6w = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 6w = 0 + -12 6w = 0 + -12 Combine like terms: 0 + -12 = -12 6w = -12 Divide each side by '6'. w = -2 Simplifying w = -2
| 18x-120=10x-72 | | 9999999999999999999999999999999999999999999999999999+99999999999999999999999999999999999999999999999999= | | F(X)=(2x-1)(x+3)(x-2) | | p=50-8x+3x^2 | | 4=52/f | | 15=-7/8(45-X) | | 3z=1.3+2.9 | | f+27=42 | | 3d+5=5-10 | | 4=6+a | | -6n+21= | | r-25=49 | | 5y+12=42 | | 0.09xX=51.29 | | m-37=49 | | 44=h-33 | | 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 |